1995
DOI: 10.1104/pp.109.3.771
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Decarboxylase Is Localized in Chloroplasts

Abstract: Plants, unlike animals, can use either ornithine decarboxylase or arginine decarboxylase (ADC) to produce the polyamine precursor putrescine. Lack of knowledge of the exact cellular and subcellular location of these enzymes has been one of the main obstacles to our understanding of the biological role of polyamines in plants. We have generated polyclonal antibodies to oat (Avena sativa L.) ADC to study the spatial distribution and subcellular localization of ADC protein in different oat tissues. By immunoblott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(68 citation statements)
references
References 25 publications
5
61
0
2
Order By: Relevance
“…In the algal and plant lineage, an alternative Put biosynthetic pathway (Fig. 2) was acquired from the chloroplast cyanobacterial progenitor, consisting of arginine decarboxylase (ADC), which produces agmatine (Agm) from arginine, agmatine iminohydrolase/deiminase (AIH), which produces N-carbamoylputrescine from Agm, and N-carbamoylputrescine amidohydrolase (NCPAH), which produces Put from N-carbamoylputrescine (27)(28)(29)(30). In addition, the same endosymbiotic source appears to have been the origin of the aminopropyltransferase thermospermine synthase (TspmSyn) (25,31), which produces the tetraamine Tspm (Fig.…”
Section: Biosynthetic Diversification Via Endosymbiotic and Horizontamentioning
confidence: 99%
“…In the algal and plant lineage, an alternative Put biosynthetic pathway (Fig. 2) was acquired from the chloroplast cyanobacterial progenitor, consisting of arginine decarboxylase (ADC), which produces agmatine (Agm) from arginine, agmatine iminohydrolase/deiminase (AIH), which produces N-carbamoylputrescine from Agm, and N-carbamoylputrescine amidohydrolase (NCPAH), which produces Put from N-carbamoylputrescine (27)(28)(29)(30). In addition, the same endosymbiotic source appears to have been the origin of the aminopropyltransferase thermospermine synthase (TspmSyn) (25,31), which produces the tetraamine Tspm (Fig.…”
Section: Biosynthetic Diversification Via Endosymbiotic and Horizontamentioning
confidence: 99%
“…The 54 kD protein may be an ADC form present only in the chloroplast of photosynthetic tissues. 33 The recognition in hop extracts of a band of a molecular mass of 24 kD using a tobacco polyclonal antibody is not surprising since it has been reported for other plant species such as oat, 34 where ADC is synthesized as a pre-protein of 66 kD, which is cleaved to produce a fragment of 42 kD (containing the original amino terminus) and a 24 kD polypeptide (containing the original carboxyl terminus), these two processed polypeptides being held together by disulfide bonds. 35 During organogenic nodule formation in hop, depending on the tissue, ADC is located in three different compartments: regulation mechanisms may be involved in ADC expression in different gene family members, plant species, tissues and physiological conditions, as well as at different developmental stages.…”
Section: Discussionmentioning
confidence: 99%
“…3 On the other hand, ADC has been reported to be regulated at the posttranslational level. 34 This indicates that different or may stimulate their oxidation through activation of DAO and PAO. Previously, it was shown an increase in lipid peroxides (precursors of jasmonates) during plantlet regeneration from organogenic nodules and related to an increase in reactive oxygen species content.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that this change in coloration of the embryo could be attributed to the fact that PAs have been detected in vacuoles, mitochondria and chloroplasts (Slocum, 1991). Borrell et al (1995) also detected these compounds in spinach thylakoid membranes, associated with lightreception complexes of the photosystem II. They concluded that the PAs maintain photosynthetic activity, thus preventing senescence due to osmotic stress.…”
Section: Effect Of Polyamines On the Efficiency And Developmental Mormentioning
confidence: 99%